APPLICATION POSSIBILITIES OF MONITORING SELECTED FACTORS OF OPERATION BY ``INTELLIGENT'' SYSTEMS IN THE VEHICLE - Holesa, Lukas; Liscak, Stefan (Doprava a spoje, 2012)
The author deals in the contribution with possibilities of monitoring of selected operation conditions for the purpose of their further extraction and analysis of impact on the fuel consumption. The attention is paid to ``intelligent'' systems in the vehicle, which are described in more detail together with their application possibilities. Particularly dynamic possibilities for monitoring operation parameters were more closely specified.